2019
DOI: 10.1177/0192623319878400
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inhaled Ambient Ultrafine Particulate Matter on Developing Brain: Potential Importance of Elemental Contaminants

Abstract: Epidemiological studies report associations between air pollution (AP) exposures and several neurodevelopmental disorders including autism, attention deficit disorder, and cognitive delays. Our studies in mice of postnatal (human third trimester brain equivalent) exposures to concentrated ambient ultrafine particles (CAPs) provide biological plausibility for these associations, producing numerous neuropathological and behavioral features of these disorders, including male-biased vulnerability. These findings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 168 publications
(230 reference statements)
0
12
0
Order By: Relevance
“…The effect on the brain from long‐term individual exposure to elevated air pollution is an inflammation‐like pathology resembling AD (Herting et al., 2019). This pathology can be detected even in younger individuals, including children, who live in cities with heavy PM pollution (Calderon‐Garciduenas et al., 2018, 2019; Cory‐Slechta et al., 2019; Power et al., 2018). Astrocytes seemed to be the main target of such disturbances (Filous & Silver, 2016) by oxygenic stress induction and ferroptosis (Lewerenz et al., 2018).…”
Section: Particulate Matter and Astrocytic Network Toxicitymentioning
confidence: 99%
“…The effect on the brain from long‐term individual exposure to elevated air pollution is an inflammation‐like pathology resembling AD (Herting et al., 2019). This pathology can be detected even in younger individuals, including children, who live in cities with heavy PM pollution (Calderon‐Garciduenas et al., 2018, 2019; Cory‐Slechta et al., 2019; Power et al., 2018). Astrocytes seemed to be the main target of such disturbances (Filous & Silver, 2016) by oxygenic stress induction and ferroptosis (Lewerenz et al., 2018).…”
Section: Particulate Matter and Astrocytic Network Toxicitymentioning
confidence: 99%
“…Suggested biological mechanisms include oxidative stress, in ammation (neuro-in ammation and systemic in ammation), neurotoxicity, and endocrine disruption [27][28][29][30] . Animal models also support developmental neurotoxicity as a plausible pathway 31,32 , and one such study has demonstrated ASD traits in mice following prenatal exposure to diesel exhaust 33 .…”
Section: Introductionmentioning
confidence: 99%
“…While it has been well-established that long-term exposure to ambient air pollution increases risk of morbidity and mortality from cardiovascular and respiratory disease [ 3 ], there is a growing literature showing that air pollutant exposure also impacts neural function and social-neurobehavioral outcomes in humans [ 4 6 ], such as autism spectrum disorder [ 7 – 11 ], bipolar disorder [ 12 ], and depression [ 13 ]. Experimental studies in animal models have supported the epidemiologic evidence, showing that in rodents, inhalation of air pollutants can lead to characteristics of neurodevelopmental and neuropsychiatric disorders [ 14 – 16 ]. Therefore, if exposure to air pollution can affect the incidence or severity of these disorders, even at ambient levels, how might air pollutants affect social behavior more generally?…”
Section: Introductionmentioning
confidence: 99%